Factor Influencing Purchase Intention among Indonesian towards Yogyakarta Fashion Product via Digital Marketing - Putri, Farahiyah Inarah; Tajuddin, Rosita Mohd.; Noh, Liza Marziana Binti Mohammad (IJBLE Scientific Publications Community Inc., 2024)
To be able to sustain in this unpredictable global situation, MSMEs in Yogyakarta must expand their sales via digital to reach more consumers. The purpose of this study was to evaluate measures and explore factors that influenced the purchase intention of local people towards Yogyakarta's local products through digital marketing. This study was guided by theory planned behaviour model approach and digital marketing mix theory. Data were collected online using Google Forms, and the snowball sampling technique was used to reach the sample. Results from the pilot test demonstrated that both adapted and self-developed measures were reliable that demonstrated an overall Cronbach alpha value of .97. The data analysis technique used Exploratory Factor Analysis (EFA). The research results showed that EFA had identified six factors (6). Findings from the analysis confirmed that the scales were reliable and validated the influence of purchase intention of local people towards Yogyakarta's local products through digital marketing. The measures enable to be applied in examining the influence of theory of planned behavior and digital marketing mix theory on purchase intention on Yogyakarta goods. This would help to generalize the data in wider scope of market such as in Indonesia.